2002
DOI: 10.1080/14763140208522787
|View full text |Cite
|
Sign up to set email alerts
|

Gymnastics

Abstract: The aim of our research was to study the relationships between performance variables in a support backward swing (SBS), which was used as a progressive step in the learning procedure for a 1 1/4 straddle-piked front somersault and the swing prior to a 1 1/4 straddle-piked front somersault from support to bent arm support on the parallel bars (5/4S). Mitja Petkovsek, parallel bars gold medallist at the 2000 EC in Bremen, performed these elements. Kinematic analysis involved CMAS software (Praha, 1993), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Teaching progressions on any element must be followed by basic pedagogic concepts, so that each progressing stage includes a movement structure similar to the desired element [45], which refers to the main practical applicability. As far as the main study limitation, authors did not have unlimited approach to some on-line archives, so only databases to which authors had total access were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching progressions on any element must be followed by basic pedagogic concepts, so that each progressing stage includes a movement structure similar to the desired element [45], which refers to the main practical applicability. As far as the main study limitation, authors did not have unlimited approach to some on-line archives, so only databases to which authors had total access were observed.…”
Section: Discussionmentioning
confidence: 99%